MOODLE y su incidencia en el aprendizaje autónomo de los estudiantes de la carrera de Pedagogía de las Ciencias Experimentales Informática de la Universidad Técnica de Babahoyo, periodo diciembre 2022 - abril 2023 - Velásquez Mendoza, Levin Martin (2023)
Autonomous learning has become a relevant issue in the educational field, since students must be able to be the protagonists of their own learning process, the main objective of this project is to determine how Moodle affects the autonomous learning of students. Students of the pedagogy career of experimental computer sciences of the technical university of Babahoyo, period December 2022 - April 2023; The inductive-deductive method will be used in order to reach coherent and original conclusions that allow an adequate interpretation of both the theoretical and empirical results obtained. This method is based on logic and will be used to reach conclusions that are consistent with the data obtained; In conclusion, it was determined that the implementation of Moodle in the Pedagogy of Experimental Computer Sciences career at the Technical University of Babahoyo has had a positive impact on the autonomous learning of students, since it has provided them with tools and resources that facilitate their process. Of learning, and has allowed them to work more collaboratively and autonomously; Fulfilling the general objective of the investigation